2012
DOI: 10.1002/path.4047
|View full text |Cite
|
Sign up to set email alerts
|

From sequence to molecular pathology, and a mechanism driving the neuroendocrine phenotype in prostate cancer

Abstract: The current paradigm of cancer care relies on predictive nomograms which integrate detailed histopathology with clinical data. However, when predictions fail, the consequences for patients are often catastrophic, especially in prostate cancer where nomograms influence the decision to therapeutically intervene. We hypothesized that the high dimensional data afforded by massively parallel sequencing (MPS) is not only capable of providing biological insights, but may aid molecular pathology of prostate tumours. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
185
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 175 publications
(194 citation statements)
references
References 65 publications
5
185
0
1
Order By: Relevance
“…Instead, multiple studies have suggested that under the selective pressure of potent AR inhibition in late-stage CRPC, PCa adenocarcinoma 'transdifferentiates' to NEPC (Lin et al 2014), which does not at all rely on AR for survival or proliferation. This transdifferentiation process is defined by a number of pathological and clinical features as well as molecular alterations that indicate the adenocarcinoma origin of NEPC, such as TMPRESS2-ERG rearrangements (Lapuk et al 2012, the loss of AR and/or AR-regulated target genes, the loss of RB1, the amplification of NMYC and AURKA, and the induction of neural differentiation programs (Beltran et al 2011, Park et al 2014. Full reviews on NEPC can be found elsewhere (Tagawa 2014, Terry & Beltran 2014, Vlachostergios & Papandreou 2015; however, in the following sections, we outline key studies that show the relationship between the NEPC transdifferentiation process and AR.…”
Section: Tumor Cell Plasticity: Neuroendocrine Transdifferentiationmentioning
confidence: 99%
“…Instead, multiple studies have suggested that under the selective pressure of potent AR inhibition in late-stage CRPC, PCa adenocarcinoma 'transdifferentiates' to NEPC (Lin et al 2014), which does not at all rely on AR for survival or proliferation. This transdifferentiation process is defined by a number of pathological and clinical features as well as molecular alterations that indicate the adenocarcinoma origin of NEPC, such as TMPRESS2-ERG rearrangements (Lapuk et al 2012, the loss of AR and/or AR-regulated target genes, the loss of RB1, the amplification of NMYC and AURKA, and the induction of neural differentiation programs (Beltran et al 2011, Park et al 2014. Full reviews on NEPC can be found elsewhere (Tagawa 2014, Terry & Beltran 2014, Vlachostergios & Papandreou 2015; however, in the following sections, we outline key studies that show the relationship between the NEPC transdifferentiation process and AR.…”
Section: Tumor Cell Plasticity: Neuroendocrine Transdifferentiationmentioning
confidence: 99%
“…Rubin's group 29 discovered that a large number of prostatic SCNCs have significant overexpression and gene amplification of Aurora kinase A and MYCN and the former may serve as a potentially useful therapeutic target Collins's group 30 found REST transcriptional complex to be critical in the development of prostatic SCNC Such diverse findings have undoubtedly increased our understanding of this important disease and collectively may eventually help to find novel therapies. On the right is a NE tumor cell in prostatic small cell carcinoma.…”
Section: Cell Of Origin and Molecular Basis Of Prostatic Small Cell Nmentioning
confidence: 99%
“…9 In biology, they have aggressive properties with increased expression of genes involved in cellular proliferation, the cell cycle, antiapoptosis, and mitosis. 10,11 A recent study used nextgeneration sequencing for molecular characterization of NE tumors of the prostate. 12 The cell cycle kinase AURKA (aurora kinase A) and MYCN are overexpressed and amplified in NE tumors.…”
mentioning
confidence: 99%